Carcinoembryonic antigen (CEA) in the normal human small intestine: a light and electron microscopic study. Issue 10 (October 1977) - Isaacson, P; Judd, M A
Abstract : An immunoperoxidase method for the demonstration of carcinoembryonic antigen (CEA) in tissues was applied to formalin-fixed paraffin embedded and glutaraldehyde-fixed resin sections of normal human small intestine. CEA could easily be demonstrated coating the surface of the small intestine, lining the crypts, and in goblet cells, indicating its presence there in considerable concentration. At the ultrastructural level CEA was localised in the glycocalyx and in mucin granules of goblet cells but not intracytoplasmically.